Building on the past: The pâtes-de-verre sculpture of Max Stewart. Issue 2 (1st October 2013) - Cummings, Keith; Stewart, Max
Professor Keith Cummings and Dr Max Stewart discuss their collaboration in an A.H.R.C.-funded project into the techniques of a glass casting process known as pâte(s)-de-verre within the works of the French pioneer of the process, Amalric Walter (1870–1959). The results of this project (completed in 2006) provided the starting point for the extension of this process, its description and publication in the form of repeatable recipes and clear scientific principles, the generation of new glass colours and their use within a personal body of glass sculpture. The article describes the journey from the original empirical investigation, through the experimental reproduction of Walter's process, the codification of that process for publication, the extension of the process through the production of new colours and additions to the casting process itself, and their use as expressive vocabulary.